2021
DOI: 10.1161/str.0000000000000357
|View full text |Cite|
|
Sign up to set email alerts
|

Care of the Patient With Acute Ischemic Stroke (Posthyperacute and Prehospital Discharge): Update to 2009 Comprehensive Nursing Care Scientific Statement: A Scientific Statement From the American Heart Association

Abstract: In 2009, the American Heart Association/American Stroke Association published a comprehensive scientific statement detailing the nursing care of the patient with an acute ischemic stroke through all phases of hospitalization. The purpose of this statement is to provide an update to the 2009 document by summarizing and incorporating current best practice evidence relevant to the provision of nursing and interprofessional care to patients with ischemic stroke and their families during the acute (posthyperacute p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 141 publications
1
41
0
Order By: Relevance
“…According to clinical investigations, the main reason for the high mutilation rate of elderly patients with cerebral arterial thrombosis is the neglect of rehabilitation nursing. In recent years, relevant studies have shown that the early rehabilitation nursing can effectively improve the patients' recovery, and the patients receiving complete systemic rehabilitation nursing have better recovery effects [ 5 , 15 ]. In addition, based on secondary stroke prevention, our hospital expects to enhance the patients' health education by the WeChat publicity and education.…”
Section: Discussionmentioning
confidence: 99%
“…According to clinical investigations, the main reason for the high mutilation rate of elderly patients with cerebral arterial thrombosis is the neglect of rehabilitation nursing. In recent years, relevant studies have shown that the early rehabilitation nursing can effectively improve the patients' recovery, and the patients receiving complete systemic rehabilitation nursing have better recovery effects [ 5 , 15 ]. In addition, based on secondary stroke prevention, our hospital expects to enhance the patients' health education by the WeChat publicity and education.…”
Section: Discussionmentioning
confidence: 99%
“…The 3 American Heart Association statements collectively provide a comprehensive update on nursing and interprofessional care of patients with acute ischemic stroke and evidence supporting care delivery actions across the care continuum. [2][3][4]…”
Section: Discussionmentioning
confidence: 99%
“…In the third statement, best practices and supporting evidence to guide nursing care of the patient with AIS in acute stroke units are presented. 4 Along with a description of best care practices in stroke units, major differences in patient outcomes between dedicated stroke units compared with nonstroke units are reviewed. In the posthyperacute and prehospital discharge phase, nurses continue to play a critical role in identifying patients at risk for clinical deterioration through their performance of ongoing observations and assessments including timely and appropriate actions in response to patients' changing health status.…”
Section: Scientific Statement Iii: Posthyperacute and Prehospital Dis...mentioning
confidence: 99%
See 1 more Smart Citation
“…iii. Use a comprehensive evidence-based stroke discharge checklist 8,17 that incorporates elements of poststroke education, including physical, mental and emotional health promotion, stroke prevention education, and discharge resources associated with successful transitions. iv.…”
Section: Future Directionsmentioning
confidence: 99%